2018
DOI: 10.1111/tid.12918
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Clostridium difficile infection in kidney transplant recipients

Abstract: Maintaining a clinically appropriate tacrolimus trough and judicious antibiotic use and selection for UTI treatment could potentially reduce CDI in the kidney transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…6,7 Unfortunately, these are relatively common within the transplant population and do not provide much of a basis for targeted prophylaxis modalities, which are needed given the potential impact of CDI on allograft outcomes. 5 In a recent study by Spinner et al, 5 the use of antibiotics for the treatment of UTI and tacrolimus levels were associated with increased risk of CDI. However, these are not modifiable because treatment of UTI in the first year after transplant is evidence based, guideline driven, and tied to mitigation of negative outcomes, as are early posttransplant tacrolimus goals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6,7 Unfortunately, these are relatively common within the transplant population and do not provide much of a basis for targeted prophylaxis modalities, which are needed given the potential impact of CDI on allograft outcomes. 5 In a recent study by Spinner et al, 5 the use of antibiotics for the treatment of UTI and tacrolimus levels were associated with increased risk of CDI. However, these are not modifiable because treatment of UTI in the first year after transplant is evidence based, guideline driven, and tied to mitigation of negative outcomes, as are early posttransplant tacrolimus goals.…”
Section: Discussionmentioning
confidence: 98%
“…3,4 Risk factors associated with CDI in renal transplant (RTX) have been described. 5,6 However the epidemiology and perioperative risk of CDI at the time of transplant surgery has not been fully elucidated. Additionally, there is a need for identification of modifiable risk factors and means to determine which patients are at highest risk and may benefit from targeted preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] A recent study at this institution also identified increased C difficile infection risk with antibiotic treatment for UTIs, AOR 4.17 (95% CI 1.12-15.54). 15 Collectively, this illustrates that the seemingly benign choice to treat ASB can lead to future infectious consequences. Due to the lack of proven benefit and increased risk for complications, antimicrobial stewardship programs are increasingly recognizing ASB treatment as an antimicrobial "never event."…”
Section: Re Sultsmentioning
confidence: 99%
“… 29 , 30 Any intervention may have to be administered for extended time periods to ensure complete clearance of the organism; this warrants additional considerations of safety and tolerability. Finally, many at-risk patients may be immunocompromised; 31 , 32 therefore, the most appropriate interventions are those that can be tolerated by these individuals as well.…”
Section: Specific Challenges For Anti- C Difficmentioning
confidence: 99%